MATHEMATICS IN CULTURAL HERITAGE: AN ETHNOMATHEMATICAL ANALYSIS OF THE ARCHITECTURE OF FORT ROTTERDAM - Ashari, Nur Wahidin (Pedagogy: Jurnal Pendidikan Matematika, 2025)
This study analyzes the application of ethnomathematics in Fort Rotterdam, Makassar, focusing on the use of numbers and measurements in architecture as symbolic representations and defense strategies. The research employed direct observation, semi-structured interviews with tour guides, and literature review of supporting documents and journals. The findings indicate that numbers are utilized in various mathematical activities, including counting the number of bastions, gates, and internal buildings; measuring the length, area, height, and wall thickness; and designing structures that serve both strategic functions and cultural meanings. Notably, the five bastions were designed to resemble a turtle, reflecting the Gowa Kingdom’s philosophy of ruling over both land and sea. The implications of these findings are significant for mathematics education, as integrating local cultural contexts and symbolism into learning can enhance conceptual understanding, problem-solving skills, learning motivation, and students’ cultural identity. The study underscores that cultural heritage sites such as Fort Rotterdam are not merely historical artifacts but also serve as contextual mathematics learning resources that enrich formal educational experiences.